Actionability Judgments Cause Knowledge Judgments. (10th August 2016) - Turri, John; Buckwalter, Wesley; Rose, David
Abstract : Researchers recently demonstrated a strong direct relationship between judgments about what a person knows ("knowledge judgments") and judgments about how a person should act ("actionability judgments"). But it remains unknown whether actionability judgments cause knowledge judgments, or knowledge judgments cause actionability judgments. This paper uses causal modeling to help answer this question. Across two experiments, we found evidence that actionability judgments cause knowledge judgments.